Bridging the Gap between Theory and Implementation: National Language Policy and Documentation of Mother Tongue - Nwachukwu, Emmanuel Lucas Nwachukwu; Joseph , Christopher (EDUPEDIA Publisher, 2023)
Language is an essential aspect of identity and culture, playing a significant role in shaping a nation's socio-political landscape. This is why nations are continuously making effort to preserve their indigenous languages. This paper investigates the grey area of theory and implementation of the national language policy in the preservation, revitalization, documentation of mother tongue. It discusses the challenges such as lack of adequate instructional materials and qualified teachers in indigenous language, facing indigenous languages in Nigeria and how the implementation of language national language policy can promote mother tongue revitalization beyond the classroom. The paper adopts Language ecology model and David Crystal's theory of language revitalization to investigate the study. The paper adopts descriptive analysis methodology, which will use current and historical data to identify gaps in the study. The paper concludes that bridging the gap between theory and implementation of national language policy in Nigeria is a complex but a necessary and essential national task that involves the government allocating resources to produce adequate instructional materials and training teachers to be qualified in teaching indigenous languages. Also government and stakeholders should intensify efforts outside the classroom, preserving mother tongue and revitalizing endangered languages requires a multifaceted approach that extends well beyond the classroom, which involves fostering a cultural environment where the language is valued and used in daily life, creating intergenerational connections, leveraging technology and documenting linguistic resources.